Immunomodulatory effects of 17-O-acetylacuminolide in RAW264.7 cells and HUVECs: involvement of MAPK and NF-κB pathways - Achoui M; Heyninck K; Looi CY; Mustafa AM; Haegeman G; Mustafa MR (Dove Medical Press, 2014)
Mouna Achoui,1 Karen Heyninck,2 Chung Yeng Looi,1 Ali Mohd Mustafa,1 Guy Haegeman,2 Mohd Rais Mustafa1 1Department of Pharmacology, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia; 2Department of Physiology, Laboratory of Eukaryotic Gene Expression and Signal Transduction, Ghent, Belgium Abstract: The terpenoid 17-O-acetylacuminolide (AA) was shown to inhibit the production of several inflammatory mediators. However, the mechanisms by which this compound elicited its anti-inflammatory activity remain to be elucidated. In this study, we analyzed the effects of AA on inflammatory gene expression in two different cell types with primordial importance in the inflammatory processes – endothelial cells and macrophages. In human umbilical vein endothelial cells, AA inhibited the expression of inflammatory proteins including the adhesion molecules intercellular adhesion molecule 1; vascular cell adhesion molecule 1; and E-selectin, as well as the release of the chemokine interleukin-8. Additionally, AA hindered the formation of capillary-like tubes in an in vitro model of angiogenesis. AA’s effects in endothelial cells can be attributed at least in part to AA’s inhibition of tumor necrosis factor alpha-induced nuclear factor of kappa light polypeptide gene enhancer in B-cells (NF-κB)’s translocation. Also, in lipopolysaccharide-stimulated macrophage-like RAW264.7 cells, AA was able to downregulate the expression of the genes cyclooxygenase 2, inducible nitric oxide synthase, interleukin-6, and chemokine (C-C motif) ligand 2. Moreover, AA inhibited the phosphorylation of nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor-alpha (IκBα), IκB kinase (IKK), and the mitogen-activated protein kinases JNK, ERK, and p38. In conclusion, the present results further support the anti-inflammatory potential of AA in different models of inflammation. Keywords: 17-O-acetylacuminolide, angiogenesis, HUVEC, MAPK, NF-κB